Spiritualising New Media: The Use of Social Media for Da'wah Purposes within Indonesian Muslim Scholars - Rusli, Nurdin (Jurnal Komunikasi Islam, 2013)
The presence of the so-called second generation of the Internet, popularly known as web 2.0, has enabled the emergence of social media for interactive and real-time communication among societies. This study focuses on the adoption of online social media for da’wah purposes. It finds that although Muslim societies have yet to get benefits from the online social media technology, some Muslim scholars have adopted the social media to deliver da’wah activities effectively. It recommends, therefore, that the social media should be adopted by Muslims to improve the scalability of their da’wah towards societies. Moreover, da’wah strategies and paradigms needs also to be redesigned in response to new advances of technology.Keywords: online social media, adoption, uses, da’wah.-----------------------------------------------------------------------Penelitian ini membahas adopsi dan penggunaan media jejaring sosial untuk berdakwah. Hasil studi ini me–nyatakan bahwa meski masyarakat Muslim belum banyak yang mengadopsi dan menggunakan media sosial untuk pengembangan dakwah, namun beberapa tokoh Muslim sudah memanfaatkannya dengan efektif. Artikel ini mereko–mendasikan para da’i untuk memanfaatkan media sosial untuk meningkatkan skalabilitas dakwah. Dalam konteks ini, perlu dilakukan redesain strategi dan paradigma dakwah dalam merespon perkembangan teknologi baru.Kata Kunci: media sosial online, adopsi, pemanfaatan, dakwah.